THE PROCEDURES AND ACTIVITIES OF TEACHING SPEAKING THROUGH PHOTOS - Risa - - (HOLISTICS, 2009)
This paper is written to find out the procedure and activities of teaching speaking through photos that support students involve in both one way communication and two ways communication. The procedures and activities cover the aspects such as: answering comparison questions, giving advice, planning ahead, asking for clarification, outlining, making eye contact, using non-verbal communication, expressing disbelief and skepticisim, taking turns, giving more information,  reasons and examples, working cooperatively, giving and getting feedback, talking about symbols, taking survey, thinking critically, building vocabulary and pronouncing. Those aspects encourage all students to be active and participate in speaking process.